Radiation dose metrics for plain head, chest, and abdomen CT scans: An initiative toward establishing institutional diagnostic reference - Dhungana, Surendra; Sharma, Keshab; Paudel, Sharmila (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Computed Tomography (CT) examinations contribute to the largest portion of radiation exposure among X-ray-based medical imaging sources. The radiation output of the scanners should be monitored and optimized periodically to reduce radiation dose to the patients. This study aimed to explore the existing radiation dose metrics for plain head, chest and abdomen CT scans for creating institutional diagnostic reference levels and compare them with available national and international data.  Methods: The CT parameters and dose metrics data were acquired from 226 patients of 15 years and above. The dose metrics, volume CT dose index (CTDIvol) and dose-length product (DLP) of plain head, chest and abdomen were obtained from the local picture archiving and communication system (PACS). The mean as well as the 2nd and 3rd quartile values of CTDIvol, DLP and effective dose were calculated. CTDIvol of the head is referenced to a 16 cm diameter standard phantom- polymethyl methacrylate, and 32 cm diameter for the chest and abdomen. The DLP values were applied to K-coefficients to find out the effective dose; ED = K x DLP.Results: The 2nd and 3rd quartile values for CTDIvol are 43, 8.5, and 9.25; 43,10.6 and 10.9 mGy respectively, for head, chest and abdomen. The 2nd and 3rd quartile DLP values are 821, 341, and 497.5; 864.1, 397.6 and 579.7 mGy-Cm. The institutional achievable (median) effective doses are 1.72, 4.77 and 7.46 mSv, and the institutional Diagnostic Reference Values (DRL) or 75th percentile values of effective dose are 1.81, 5.56 and 8.69 mSv for head, chest and abdomen respectively.Conclusions: The dose metrics of the plain head, chest and abdomen were reported for creating an institutional DRLs and compared to available national and international data. This study points to the need for optimization of the chest and abdomen protocol; chest protocol for relatively higher CTDIvol and DLP values and abdomen for a higher DLP value.